(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Micropaleontology can give important insights into the provenance and paleoenvironmental conditions in terrestrial sedimentary archives. For the current study, 84 samples representing a 2.6 km thick sedimentary profile from the SimplyFolded Zagros Mountain Belt were investigated. They span ca. 10.2 my from the late Middle Miocene (Serravallian) to the earliest Pleistocene (Gelasian), and comprised floodplain sediments and saline mudstones with an aeolian contribution. The mudstones revealed a unique Cretaceous radiolarian assemblage comprising largely of cryptothoracic Nassellarians and spherical spumellarians. This record highlights the reworking of sediments derived from Cretaceous Qulqula- Kermanshah radiolarian claystones and radiolarites in the Imbricated Zagros belt into the distal Neogene Zagros foreland sediments in Lurestan (Lurestan Arc). The high abundance of Holocryptocanium barbui (Dumitrica) and other cryptothoracic taxa compared to the Qulqula- Kermanshah radiolarian claystones and radiolarites potentially indicates a preferred erosion of softer units such as the Red Radiolarian Claystone Unit (RRCU) compared to harder radiolarian cherts. The observation of a reworked largely cryptothoracic assemblage might also point to additional sorting effects during fluvial and aeolian transport as well as during redeposition, depending on the morphology and hydrodynamic properties of individual radiolarian taxa.